2020
DOI: 10.21203/rs.3.rs-42052/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compositional and drug-resistance profiling of pathogens in patients with severe acute pancreatitis: a retrospective study

Abstract: Background: Infection is one of the important causes of death in patients with severe acute pancreatitis (SAP) , but the bacterial spectrum and antibiotic resistance are constantly changing. Making good use of antibiotics and controlling multi-drug-resistant (MDR) bacterial infections are of vital importance in improving the cure rate of SAP. We conducted a retrospective study in the hope of providing references for antibiotic selection and control of drug-resistant bacteria. Methods: Retrospective analysis wa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Overused prophylactic antibiotic treatments for 'suspected' IPN could result in the acquisition of MDR or carbapenem resistance [1]. Precious studies reported that CRE, as a mainly infectious MDR pathogen, has spread worldwide and influenced the outcome of IPN patients especially in India and China [7,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overused prophylactic antibiotic treatments for 'suspected' IPN could result in the acquisition of MDR or carbapenem resistance [1]. Precious studies reported that CRE, as a mainly infectious MDR pathogen, has spread worldwide and influenced the outcome of IPN patients especially in India and China [7,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Shenvi et al found that markers of inflammation may be helpful to determine the timing and choice of IPN therapeutic intervention [18]. Despite recent clinical research focused on MDR IPN among AP patients, there are still important knowledge gaps and a lack of accurate clinical data among the CRE IPN population [7,8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Patients' pancreas will have various complications such as bleeding and necrosis, multiple organ failure, secondary infection, peritonitis and shock. The incidence is as high as 40%-70% (5), and the mortality is about 7%-47% (6,7). AP is a common disease in emergency department, which is dangerous and develops rapidly.…”
Section: Introductionmentioning
confidence: 99%